2021
DOI: 10.1093/cid/ciab067
|View full text |Cite
|
Sign up to set email alerts
|

Transcontinental Dissemination of the L2b/D-Da Recombinant Chlamydia trachomatis Lymphogranuloma venereum (LGV) Strain: Need of Broad Multi-Country Molecular Surveillance

Abstract: Previously, we identified a Chlamydia trachomatis Lymphogranuloma venereum (LGV) recombinant strain possessing a unique non-LGV ompA genotype. Here, culture-independent genome sequencing confirms its circulation in Europe, Middle East and North America, and unveils genetic evidence of emergence of antibiotic resistance. Multi-country and systematic molecular surveillance is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Similarly, recent evidence has suggested that clinically relevant recombination events have occurred between two C. trachomatis strains (serovar D and LGV). Recent outbreaks of LGV (L2b strain) within men who have sex with men (MSM) populations have resulted in genetic recombination of the omp A gene from non-LGV strains ( Borges et al., 2019 ; Borges et al., 2021 ). A previously undetected outbreak of LGV may have gone undiagnosed due to over- reliance on the omp A gene for identification.…”
Section: Whole Genome Phylogenies Resolve Fine-detail Relationships B...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, recent evidence has suggested that clinically relevant recombination events have occurred between two C. trachomatis strains (serovar D and LGV). Recent outbreaks of LGV (L2b strain) within men who have sex with men (MSM) populations have resulted in genetic recombination of the omp A gene from non-LGV strains ( Borges et al., 2019 ; Borges et al., 2021 ). A previously undetected outbreak of LGV may have gone undiagnosed due to over- reliance on the omp A gene for identification.…”
Section: Whole Genome Phylogenies Resolve Fine-detail Relationships B...mentioning
confidence: 99%
“…Further genomic analysis found that the C. trachomatis L2B strain had undergone genetic recombination, acquiring omp A from the non-LGV strain C. trachomatis D-Da ( Borges et al., 2019 ). Furthermore, follow-up studies have indicated that this L2b/D-Da variant is spreading across Europe and, with the continued reliance on omp A for strain identification, the probability of further dissemination across the globe is high ( Borges et al., 2021 ).…”
Section: Whole Genome Phylogenies Resolve Fine-detail Relationships B...mentioning
confidence: 99%
“…The ompA gene of C. trachomatis can be inserted into different genomic backbones through potential gene recombination. However, the recombination of ompA may happen most likely between L strain and I/J/K strains or between ocular and urogenital branches or between L2b and D-Da strains ( Somboonna et al, 2011 ; Harris et al, 2012 ; Matičič et al, 2016 ; Borges et al, 2021 ). Hadfield et al (2017) reported that in their comprehensive global genome dynamic analysis of C. trachomatis , only serovar D and J appeared in both monophyletic lineage T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
“…These problems contribute to the silent spread of this microorganism ( Martínez-García et al, 2021 ). Therefore, improved screening ( Rodríguez-Domínguez et al, 2022 ) and discovery of new genetic markers, which can be easily implemented in molecular surveillance, could help better understand the LGV epidemic ( Borges et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%